Monitoring water molds in northern Baltic rivers and salmon : Applicability of eDNA methods to detect Saprolegnia parasitica in river environments - Härkönen, Laura S.; Iso-Touru, Terhi; Kinnula, Hanna; Rask, Marjukka; Korkea-aho, Tiina (Luonnonvarakeskus, 2024)
During the last decade, water molds, especially Saprolegnia parasitica, have been associated with salmon deaths in rivers around the Northern Baltic Sea. At present, knowledge of the distribution of S. parasitica and its abundance in these rivers and in different salmonid species is limited. In this project, we developed a sampling and detection method to monitor the presence of S. parasitica in river water using environmental DNA (eDNA) analysis. Salmonid fish and water samples were collected along the River Tornionjoki from summer to late fall in 2022–2023 and, as a reference to validate the eDNA methods, from the River Oulujoki in the year 2022. For the eDNA analysis of S. parasitica from water samples, we used two different detection methods simultaneously, i.e. real-time quantitative PCR (qPCR) assay and digital PCR (dPCR) assay. We found that the dPCR based detection is more sensitive than the qPCR, and thus more applicable for S. parasitica detection from natural river waters. During the study years 2022‒2023, S. parasitica DNA was detected in water samples from the River Tornionjoki, although we had no evidence on S. parasitica infection in salmonids. However, we detected other aquatic fungi than S. parasitica that were responsible for skin lesions in some of the studied salmonids. On the contrary, both salmon and brown trout with a S. parasitica infection were confirmed from the nearby River Oulujoki, where also the variation in S. parasitica DNA concentrations in water samples aligned well with the observed numbers of symptomatic fish. Based on current results, the eDNA is a promising method for monitoring the presence and concentrations of S. parasitica in river environments. However, further research is still needed to apply eDNA results for predicting the health consequences for wild salmonid populations.
Keywords: Atlantic salmon; Brown trout; water mold; Saprolegnia parasitica; environmental DNA; River Tornionjoki; River Oulujoki